Reconfigurable on-board power Processor with wired and wireless Charging for electric vehicles - Meher, Soumya Ranjan (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Reconfigurable on-board; power Processor; with wired and wireless; Charging for electric vehicles